Analisis Zat Gizi dan Mutu Oranoleptik Subsitusi Tepung Ubi Jalar Ungu (Ipomoe Batatas) pada Cookies sebagai Selingan Tinggi Serat untuk Penderita Diabetes Melitus - Septi Muda Cahyaning Tyas; Lilia Faridatul Fauziah (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Background: Diabetes Mellitus (DM) is one of the many degenerative diseases that is currently a serious concern in developing countries, especially like Indonesia. Diabetes mellitus is a condition where blood sugar levels are higher than normal. Diabetes mellitus is a metabolic disorder characterized by chronic hyperglycemia, namely loss of function of the body's organs, especially the eyes, kidneys, nerves, heart and blood vessels due to damage to insulin secretion. Diabetes mellitus cannot be cured but can be prevented and controlled through diabetes mellitus management such as diet, physical exercise, medication, counseling, and monitoring blood sugar. Whether the treatment of diabetes mellitus is successful or not depends on the sufferer himself. If you do not carry out good control discipline, your blood sugar levels will always be high and will cause various kinds of complications. Because the body does not have enough insulin hormone due to interference with insulin secretion, the insulin hormone does not work as it should or both. Considering the large negative impact of diabetes mellitus, it needs to receive sufficient attention. Therefore, additional food is needed that can maintain blood glucose levels in the body. The aim of this research was to determine the effect of substitution of purple sweet potato flour in cookies on organoleptic quality and fiber content on the effect of substitution of purple sweet potato flour.